The modern tontine: An innovative instrument for longevity risk management in an aging society - Jan-Hendrik Weinert; Helmut Gründl (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2016)
The changing social, financial and regulatory frameworks, such as an increasingly aging society, the current low interest rate environment, as well as the implementation of Solvency II, lead to the search for new product forms for private pension provision. In order to address the various issues, these product forms should reduce or avoid investment guarantees and risks stemming from longevity, still provide reliable insurance benefits and simultaneously take account of the increasing financial resources required for very high ages. In this context, we examine whether a historical concept of insurance, the tontine, entails enough innovative potential to extend and improve the prevailing privately funded pension solutions in a modern way. The tontine basically generates an age-increasing cash flow, which can help to match the increasing financing needs at old ages. However, the tontine generates volatile cash flows, so that - especially in the context of an aging society - the insurance character of the tontine cannot be guaranteed in every situation. We show that partial tontinization of retirement wealth can serve as a reliable supplement to existing pension products.
Keywords: D14; D91; G11; G22; H75; J11; J14; 330; Life Insurance; Tontines; Annuities; Asset Allocation; Retirement Welfare; Aging Society